Communication Perspective on the Acceptance of the Lombok Muslim Community towards the Da'wah Activities of the Tablighi Jamaat - Irpan Irpan (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
The purpose of the study was to determine the driving factors for the acceptance process of the Lombok Muslim community towards the da'wah of the Tablighi Jamaat. This is based on the reality of da'wah, which shows a movement against the activism of transnational da'wah movements. The research was conducted through a qualitative approach—data collection techniques through participant observation, unstructured interviews, and documentation. Data analysis follows the stages of the Miles, Huberman, and Saldana interactive model. The study's results stated that the acceptance of the Lombok Muslim community towards the Tablighi Jamaat was due to the good social interaction between the Tablighi Jamaat community and the Lombok Muslim community. Including strengthening teachings, namely the importance of reviving the sunnah of the prophet, conveying greetings, the essence of brotherhood, the urgency of praying in congregation, and turning on the knowledge assembly. The da'wah approach is carried out through distance or friendship and the attitude of glorifying others (Ikram). The communication used is empathic and persuasive. The implication of the research shows that all levels of society can reasonably respond to da'wah politely and with a noble purpose. In addition, at a particular stage, the mindset and behavior of the community can be formed in carrying out Amar makruf nahi munkar.